2019
DOI: 10.1542/hpeds.2018-0103
|View full text |Cite
|
Sign up to set email alerts
|

Encounters From Device Complications Among Children With Medical Complexity

Abstract: A B S T R A C TOBJECTIVES: Children with medical complexity (CMC) are commonly assisted by medical devices to support essential body functions, although complications may lead to preventable emergency department (ED) and hospital use. Our objective was to identify predictors of device-complicated ED visits and hospitalizations.METHODS: This single-center retrospective cohort study included patients referred to a Pediatric Complex Care Program between April 1, 2014, and April 30, 2016, assisted by at least 1 me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…Most CMC require the use of medical devices, such as tracheostomies and enteral feeding, yet device complications are common and have been associated with frequent emergency department visits or hospitalizations (Berry et al, 2011;Nackers et al, 2019). Our research found that device complications account for 17% of overall hospitalizations and 30% of overall emergency department (ED) visits for children in our pediatric complex care program (Nackers et al, 2019).…”
Section: Participatory Design Of a Mobile Application To Support Family Caregivers Of Children With Medical Complexity Who Require Enteramentioning
confidence: 82%
“…Most CMC require the use of medical devices, such as tracheostomies and enteral feeding, yet device complications are common and have been associated with frequent emergency department visits or hospitalizations (Berry et al, 2011;Nackers et al, 2019). Our research found that device complications account for 17% of overall hospitalizations and 30% of overall emergency department (ED) visits for children in our pediatric complex care program (Nackers et al, 2019).…”
Section: Participatory Design Of a Mobile Application To Support Family Caregivers Of Children With Medical Complexity Who Require Enteramentioning
confidence: 82%
“… 3 Device complications appear to comprise a sizable proportion of overall ED and hospital use for CMC, with one previous study suggesting as much as 17% of total hospitalizations for CMC with medical devices were due to device complications in the year before enrollment in a complex care program. 1 One of the only other studies to quantify the proportion of hospitalizations attributed to medical device complications observed that 9% of hospitalizations for CMC were due to medical device complications 2 ; however, those children were already enrolled in a complex care program.…”
Section: Discussionmentioning
confidence: 99%
“…Visits likely related to device complications were identified using a method previously described. 1 Three reviewers (a trained research assistant and two physician reviewers, each with over 10 years of complex care experience) established high interrater reliability (Kappa = 0.92).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 As such, enteral tube complications can make up a sizable proportion of overall ED and hospital use experienced by CMC. 2,12 Mobile health (mHealth) and mobile applications (apps) have the potential to support CMC enteral tube care, prevent complications, and improve child and family outcomes by serving as a portable resource and organizational tool to improve collaborative symptom tracking, monitoring, and management of chronic conditions and improve caregiver communication. [13][14][15] Although apps to support caregiving exist, most are designed to support patients with less complex conditions (eg, asthma, diabetes), and their impact on health outcomes is poorly understood.…”
mentioning
confidence: 99%